Media will never influence learning - Clark, Richard E. (Educational Technology Research and Development, 1994)
The purpose of this discussion is to explain and sharpen different points of view about the impact of media and attributes of media on learning, motivation and efficiency gains from instruction. This paper is an attempt to summarize my arguments about the research and theory in this area and to respond to Robert Kozma's criticism of my earlier discussion of these issues. I will first briefly summarize my arguments about media effects; next I will attempt to characterize the many reactions to the controversial claim that media do not influence learning or motivation. Finally, I will respond to the specific criticisms advanced by Robert Kozma this issue.
Keywords: Early Discussion; Educational Technology; Efficiency Gain; Media Effect; Specific Criticism